A study on seroprevalence of HIV among women attending obstetric care in a tertiary care hospital of South India with maternal and perinatal outcomes - M. N., Shruthi; Jois, Srinivas K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: HIV is prevalent in epidemic proportions in India. Identifying the target population and effective intervention reduces chances of vertical transmission and new infection. Authors studied the seroprevalence of HIV among women attending obstetric care in a tertiary care hospital of South India and associated maternal and perinatal outcomes among seropositive women. Methods: Retrospective descriptive study of all women who were screened for HIV at Integrated Counselling and Testing Centre, Vani Vilas hospital, from January 2014 to December 2017 in their antenatal, intranatal and postnatal period. Demographic data of seropositive women, obstetric outcomes and status of children at 18months were obtained. Results: Of the 35,455 women who were screened, 0.28% were found positive for HIV. Percentage prevalence of HIV was highest in 2014 (0.32%). Majority of the seroprevalence belonged to age group of 25-29 years (44%), 32% illiterates, 82% homemakers and 79% belonged to urban areas. Unknown partner status in 22% and majority were diagnosed in antenatal period (66%). Of them 82% had favourable CD4 count. 74 % of them delivered live baby. Three maternal deaths were observed and anaemia (65%) was the major associated co-morbidity. Vaginal route was common mode of delivery (84%). Thirteen babies required NICU admission and 6 neonates deaths were encountered. Exclusive breastfeeding was practised in 91% of live births. 62% of children were found seronegative at 18 months follow up. Conclusions: Authors observed with adequate treatment to mother and prophylaxis to the baby, the burden of vertical transmission can be significantly reduced.